Synthesis of chitosan based new material for recovery of Pt (IV) - Majigsuren, Enkhtuya; Byambasuren, Ulziidelger; Yunden, Gachimeg; Shirendev, Nasanjargal; Tserendorj, Chuluuntsetseg; Bat-Amgalan, Munkhpurev; Kano, Naoki (Journal of Applied Science and Engineering A, 2023)
In this study a new type of adsorbent bead precursor was reached using chitosan and pretreated clay. The pretreated clay was produced from the clay of the "Tsogt-Ovoo" deposit in the Umnugovi province of Mongolia. It was produced by acid and heat treatment to remove its mechanical impurities. The mixtures of chitosan and pretreated clay were taken with various ratios (8:1, 8:2, and 8:3) for chemical processing to obtain a chitosan-based adsorbent bead for recovery of (Pt(IV)) from aqueous solution. It was examined that the adsorption capacity of the adsorbent bead when the chitosan and pretreated clay mass ratio 8:2 was the highest for platinum ion (Pt (IV)). The adsorption properties of Pt (IV) were studied depending on the solution pH, contacting time, temperature, initial concentration of platinum ion solution, and amount of adsorbent material. The adsorption efficiency was the highest (93.29%) when the initial concentration of the platinum ion was 50 mg/l at the following condition; pH=3, temperature 250C, time 3 hours, and the amount of the adsorbent material 0.1 g. It represents that the chitosan clay bead can be applied for the recovery of platinum (Pt (IV)) from aqueous solution.